Fatigue Life Assessment and Reliability Analysis of Cope-Hole Details in Steel Bridges - Ping Liao; Yongbao Wang; Xiucheng Zhang; Renda Zhao; Yi Jia; Haifeng Zhu (The Baltic Journal of Road and Bridge Engineering)
Cope-hole details are widely applied to steel bridges. However, the safety of steel bridges is influenced by the fatigue performance of welded details. So, cope-hole details with flange and web subjected to axial loads were selected as the research object. Based on the basic theory of linear elastic fracture mechanics and the Finite Element Method, the stress intensity factors of cope-holes details were calculated. The influences of geometry size and crack size of the detail on the stress intensity factors were then investigated. The Paris model of fatigue crack propagation predicted the crack propagation life of cope-hole details. Besides, the fatigue limit-state equation was also established to analyse the effect of random variables (such as initial crack size, critical crack size, crack propagation parameter) on the fatigue reliability index. Finally, the recommended value of the detection period was present. The results show that the stress intensity factor gradually increases with the increase of the cope-hole radius, the weld size, the flange plate thickness, the crack length and the web thickness. However, it gradually decreases with the increase of the ratio of the long and short axle to the crack. The predicted number of fatigue cyclic loading required by the fatigue crack depth propagating from 0.5 mm to 16 mm under nominal stress amplitude of 63 MPa is 122.22 million times. The fatigue reliability index decreases with the fatigue growth parameter, the crack shape ratio and the mean of initial crack size increasing, which is relatively sensitive. However, the variation coefficient of the initial crack size has little effect on it. The detection period of cope-hole details is the service time corresponding to the fatigue accumulated cyclic loading of 198.3 million times.